Transformative Learning Through an Online Global Class Project in Teacher Education. Issue 2 (3rd April 2018) - Kim, Jiwon; Wong, Chiu-Yin; Lee, Yongjin
ABSTRACT: This exploratory research study aimed to understand teacher candidates' experiences and perspectives in a global class project and to explore a way to develop global understanding in a teacher education program, by means of technology rather than study abroad. Using a qualitative approach, seven U.S. education majors were given opportunities to communicate online with teacher candidates in South Korea, while creating and discussing a concept map and movie presentation about "good teaching" on the Learning Management System. Results showed how the preservice teachers' global perspectives of education were developed through the project, and confirmed the significance of instrumental and communicative learning in transformative learning as well as direct communication and comparison with people from a different context using a carefully designed task-based course and immersive learning environment.